Nitric oxide is involved in the hypothyroidism with significant morphology changes in female Wistar rats induced by chronic exposure to high water iodine from potassium iodate. (September 2018) - Rong, Shengzhong; Gao, Yanhui; Yang, Yanmei; Shao, Hanwen; Okekunle, Akinkunmi Paul; Lv, Chunpeng; Du, Yang; Sun, Hongna; Jiang, Yuting; Darko, Gottfried M.; Sun, Dianjun
Abstract: Epidemiological studies indicated that chronic exposure to high water iodine is associated with primary hypothyroidism (PH) and subclinical hypothyroidism (SCH). However, the mechanism is not well understood. In this study, we explored whether chronic exposure to high water iodine from potassium iodate (KIO3 ) can induce hypothyroidism in addition to determining if nitric oxide (NO) is involved in the pathogenesis. 96 female Wistar rats were divided into six groups: control, I1000μg/L, I3000μg/L, I6000μg/L, N-nitro-L-arginine methylester (L-NAME) and L-NAME+I6000μg/L . After 3 months, urine iodine concentration, thyroid hormone, NO and nitric oxide synthase (NOS) serum levels were determined. Additionally, thyroid expression of inducible nitric oxide synthase (iNOS) was also investigated. Thyroid morphology was observed under light microscopy and transmission electron microscope. SCH as indicated by elevated serum thyrotropin (TSH) was induced among rats exposed to 3000 μg/L I -, while rats treated with 6000 μg/L I - presented PH characterized by elevated TSH and lowered total thyroxine in serum. Moreover, serum NO, NOS and iNOS expression in the thyroid were significantly increased in I3000μg/L and I6000μg/L groups. Changes in thyroid function and morphology in the L-NAME+I6000μg/L group were extenuated compared to I6000μg/L group. These findings suggested that chronic exposure to high water iodine from KIO3 likely induces hypothyroidism with significant morphology changes in female Wistar rats and NO appears to be involved in the pathogenesis. Graphical abstract: Image 1 Highlights: High water iodine induced hypothyroidism in female Wistar rats. Serum NO and NOS increased with high water iodine in female Wistar rats. The iNOS expression in the thyroid of rats increased with high water iodine. Inhibition of NO alleviated effects of high water iodine on the thyroid of rats.